Fracture mechanics - Perez, Nestor, 1950- (Springer, 2016)
The second edition of this textbook includes a refined presentation of concepts in each chapter, additional examples; new problems and sections, such as conformal mapping and mechanical behavior of wood; while retaining all the features of the original book. The material included in this book is based upon the development of analytical and numerical procedures pertinent to particular fields of linear elastic fracture mechanics (LEFM) and plastic fracture mechanics (PFM), including mixed-mode-loading interaction. The mathematical approach undertaken herein is coupled with a brief review of several fracture theories available in cited references, along with many color images and figures. Dynamic fracture mechanics is included through the field of fatigue and Charpy impact testing. Explains computational and engineering approaches for solving crack-related problems using straightforward mathematics that facilitate comprehension of the physical meaning of crack growth processes; Expands computational understanding with theoretical concepts and detailed treatments of formula derivation; Presents analytical methods for deriving stress and strain functions related to fracture mechanics; Reinforces concepts and modeling techniques with example problems that support comprehension and application of a particular theory.- Resumé vydavatel
Keywords: lomová mechanika; fracture mechanics; elektronické knihy; učebnice vysokých škol; electronic books; textbooks (higher)